ответ 4
https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%203x%2B14%20%5Cgeq%204-x%20%5C%5C%20%5C%5C%20%5Cfrac%7B5x-1%7D%7B4%7D%20-%20%5Cfrac%7Bx-1%7D%7B2%7D%20%5Cgeq%203x-2%2C%20~%20%5CBig%20%7C%5Ctimes%204%20%5Cend%7Barray%7D%20%5Cright.%20%5C%5C%20%5C%5C%20%5C%5C%20%5C%5C%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%203x%2Bx%20%5Cgeq%204-14%20%5C%5C%20%5C%5C%20(5x-1)%20-%202(x-1)%20%5Cgeq%204(3x-2)%20%5Cend%7Barray%7D%20%5Cright.%20%5C%5C%20%5C%5C%20%5C%5C%20%5C%5C%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%204x%20%5Cgeq%20-10%20%5C%5C%20%5C%5C%205x-1%20-%202x%2B2%20%5Cgeq%2012x-8%20%5Cend%7Barray%7D%20%5Cright.
2sin^2x-2sinxcosx=cos^2-sin^2x,
2sinx*(sinx-cosx)+sin^2x-cos^2x=0,
2sinx(sinx-cosx)+(sinx-cosx)*(sinx+cosx)=0,
(sinx-cosx)(2sinx+sinx+cosx)=0,
(sinx-cosx)(3sinx+cosx)=0
1. sinx-cosx=0, sinx=cosx, tgx=1
x=pi/4+pi*k, k-целые
2. 3sinx+cosx=0, 3sinx=-cosx, tgx=-1/3
x=arctg(-1/3)+pi*k, k-целые
2)cos3x+cosx=0,
4cos^3x-3cosx+cosx=0,
4cos^3x-2cosx=0,
4cosx(cosx-√2/2)(cosx+√2/2)=0
1. cosx=0, x=pi/2+pi*k, k-целые
2. cosx=√2/2, x=+-pi/4+2pi*k
3. cosx=-√2/2, x=+-3pi/4+2pi*k
Корни из промежутка [-pi/2;pi/2]:
x=-pi/2, x=pi/2, x=-pi/4, x=pi/4